(untitled) (Medical Forum Monthly, 2024)
Objective: The objective of this study was to assess the role of ultrasound in the diagnosis of acute appendicitis and its correlation with neutrophil count. Study Design: Descriptive study. Place and Duration of study: This study was conducted at the Department of Radiology, Bolan Medical Complex Hospital, Quetta from September 2016 to June 2017. Materials and Methods: A total 70 patients were selected from emergency and outdoor departments of Bolan Medical complex Hospital Quetta. The patients were presented with pain and tenderness in right lower quadrant. Ultrasound findings were correlated with neutrophil count. Results: Total of 70 patients in which 35 (50%) were males and 33 (47%) were females. 56(80%) patients presented with acute appendicitis, 4(6%) with appendicular abscess, 7(10%) with appendicular lump and 3(4%) patients with appendicular rupture. The most common age presentation was 11-20 years 31 (44%), the least common age presentation was 41 years and above 2 (3%), 21-30 year range was 18(26%), 0-10 years range was 16 (23%) and from 31-40 years was 3 (4%). Patients with increased neutrophil (Neutophilia) count were seen in 63 (90%) and with normal neutrophil count were 7 (10%). Conclusion: Ultrasound is safe, easily available and effective tool in the diagnosis of acute appendicitis.